Study of the сhemical composition of cranberry and the use of berries in food technology - Khomych, Galyna; Matsuk Yuliiа; Nakonechnaya, Julia; Oliynyk Nataliа; Medved, Lolita (Eastern-European Journal of Enterprise Technologies, 2017)
We investigated the ingredient composition of fractions of phenolic compounds of cranberries gathered in Ukraine and its change depending on methods of fermentolysis in the production of juice. The studies showed that the use of complex action enzymes for pretreatment of raw material makes it possible to enrich finished product with physiologically active ingredients of raw material by adjusting the activity during fermentolysis of endo- and exo-enzymes. We established that we can expect the best results in the case of instantaneous warming of squash after enzymatic treatment. We determined that significant content of phenolic substances remains in the waste of juice production – in squash. The complex processing of cranberries with the use of cranberry juice in the technology of fruit sauces, as well as high-quality juice production, is offered in the technology of nonalcohol beverages and meat pastes. The use of cranberry juice in fruit sauces provides product with a pleasant color, prevents darkening of bananas during processing. The use of water-alcohol extracts produced from squash makes possible to avoid the use of artificial coloring agents in the production of nonalcohol beverages. The use of powder made of dried cranberry squash in the receipt of paste products increases moisture binding capacity of meat and the output of a finished product. The study shows that the use of cranberries for the production of food products will make it possible to enrich chemical composition, to compensate for the deviation in functional and technological properties of raw material and to introduce resource-saving technologies